Estratégias ideológicas no discurso eleitoral para o governo do estado de Pernambuco: um olhar da ACD - Felipe, Leonardo Ariel Grosskreutz (2015)
This research is a qualitative, analytical and documentary study in the light of Critical Discourse Analysis (CDA). Investigates the discursive strategies present in the campaign to dispute the power to the State Government of Pernambuco 2014. As a goal we intend to investigate the verbal and nonverbal features of the election campaign for the state government, an ideological manipulation strategy to maintaining hegemony. Thus, the media will be investigated tactics winner of the last election through the delimitation of the corpus, this consists of a kind of genre pictures, the "holy card". Distributed in the electoral race the holy card bearing the candidate's image and is used as a proxy tool even with its voter. The study is based on the concepts of displacement and concealment of political figures, to enhance the candidate's figure, presented by Thompson (1995). The vision of ideology as the spirits of the past, presented by Marx and Engels, and the latent conception of ideology by Thompson (1995) help to understand the relationships of power and domination. Is indispensable therefore understand how the ideology and ideological apparatuses explained by Gramsci (1966), Althusser (1983) and Santos (1987). Bobbio (1995) and Giddens (1996) helps to understand the way in which the notion of right and left shapes the political reality and structure the hegemonic process. Therefore, this dissertation aims to contribute to society and to the historical moment of struggle of the population by structural improvements in policy. The paper also attempts to contribute to an understanding of the relationships, often silent, domination to which the electorate is subjugated. The fundamentals of analysis and understanding of speech presented by Critical Discourse Analysis (CDA) will look for a more thorough discursive practice of the candidate and the ideological apparatuses, according Fairclough (2001). The Social Semiotics and studies, on Multimodality, present the metafunctions as grammatical components of semantic characterization. It also shows the use of verbal and visual contributing to the captivating strategy in the speech of holy cards. Sometimes the markers and metafunctions indicate the action to move forward in other mask partisan historical, disclosed in a bibliographic research pointing alliances and coalitions in the last 30 years in Pernambuco. Already as verbal and visual discourse markers will be used those of the ACD for text analysis and Design Visual Grammar (GDV), the authors Günter Kress and Theo Von Leeuwen (2006), for image analysis. Through research on imagery and textual speech, full of ideology, the thesis points to the maintenance of local hegemony. In this sense is shown using symbols and historical figures appear next to a text by simple but very elaborate times, thus contributing to shape a winning strategy in the electoral race.